1996
DOI: 10.1164/ajrccm.154.1.8680680
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an anti-CD3 monoclonal antibody on bleomycin-induced lymphokine production and lung injury.

Abstract: Acute lung injury was produced in C57BL/6 mice by the intratracheal (i.t.) administration of bleomycin (BLM). Following injection of 0.1 U BLM, CD3+ lymphocytes and the production of the T-helper-1 (Th1) lymphokines interleukin-2 (IL-2) and interferon-gamma (IFN-gamma) were increased in lung and lymph nodes. The production of the Th2 cytokine IL-4 by lung lymphocytes was decreased. Intraperitoneal (i.p.) injection of a rat antimurine CD3 (YCD3) monoclonal antibody (mAb) blocked the accumulation of pulmonary CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
69
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 20 publications
10
69
1
1
Order By: Relevance
“…46 -48 A role for IFN-␥ in bleomycin-induced interstitial fibrosis is supported by the observations that susceptible versus non-susceptible mouse strains produce high amounts of IFN-␥, 42 depletion of T cells down-regulates both IFN-␥ expression and fibrosis, 35,49 and high levels of IFN-␥ expression and fibrosis are observed in SCID mice, which are susceptible to bleomycin-induced fibrosis. 42 Bleomycin treatment of IFN-␥ knockout mice (IFN-␥ -/-) also resulted in both a significant inhibition of pulmonary inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…46 -48 A role for IFN-␥ in bleomycin-induced interstitial fibrosis is supported by the observations that susceptible versus non-susceptible mouse strains produce high amounts of IFN-␥, 42 depletion of T cells down-regulates both IFN-␥ expression and fibrosis, 35,49 and high levels of IFN-␥ expression and fibrosis are observed in SCID mice, which are susceptible to bleomycin-induced fibrosis. 42 Bleomycin treatment of IFN-␥ knockout mice (IFN-␥ -/-) also resulted in both a significant inhibition of pulmonary inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of type 2 cytokine production has been demonstrated in animal models of pulmonary fibrosis (14,17) and in animal models of dermal fibrosis (82). Type 2 cytokine production can lead to pulmonary fibrosis through multiple pathways, including 1) the direct stimulation of extracellular matrix production in fibroblasts by IL-4 (31,32); 2) the indirect stimulation of collagen production by IL-5, through effects on eosinophils (33); 3) the absence of antifibrotic effects of IFN␥ (34); and 4) alternative activation of macrophages, which become profibrotic cells (83).…”
Section: Discussionmentioning
confidence: 99%
“…This network includes, but is not limited to, epithelial cell apoptosis, T cell activation, inflammatory cell influx, latent TGF␤ activation, increased production of type 2 cytokines and monocyte chemotactic protein 1 (MCP-1), reduced prostaglandin E 2 production, an activated coagulation cascade, myofibroblast transformation, and increased extracellular matrix production (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). T cells are essential to the development of pulmonary fibrosis induced by bleomycin, silica, trinitrophenyl hapten, or radiation (13)(14)(15)(16)(17)(18)(19). In all these models of acute lung damage, there is a predominance of early lymphocyte infiltrates in the lungs (13)(14)(15)(16).…”
Section: Group 1 Suggested the Possibility That These T Cells Might Imentioning
confidence: 99%
See 1 more Smart Citation
“…We have chosen to focus on the bleomycin model, as intratracheal instillation of bleomycin into rodents has provided important insights into the molecular pathways leading to fibrotic responses to lung injury (Supplemental Table S1). Limitations of the bleomycin model include the following: 1) the findings in mice are strain dependent, and Haston et al (67) have shown that many of these strain-related differences might be explained by differential expression of bleomycin hydrolase (67,134); 2) the prominent proinflammatory response following bleomycin may not be present in human IPF (115,136,153); and 3) the time course of bleomycin-induced fibrosis is selflimited, whereas human IPF is often an inexorably progressive disease (121).…”
Section: L491mentioning
confidence: 99%